THE INFLUENCE OF MICRO SMALL AND MEDIUM ENTERPRISE TAX COMPLIANCE LEVEL ON REGIONAL TAX REVENUE PAKPAK BHARAT DISTRICT - Renika Hasibuan; Anggi Pratiwi Sitorus; Enda Nurlinta Padang (PT. Radja Intercontinental Publishing, 2023)
This research aims to examine the effect of MSME taxpayer compliance on regional tax revenues in Pakpak Bharat district. The sampling technique in this research was carried out using probability sampling and non-probability sampling methods. With a population of 1940 MSMEs. The data collection technique used was by distributing questionnaires to 95 MSMEs in Pakpak Bharat district which consists of 8 sub-districts. Based on the results of the research, it was found that the compliance of MSME taxpayers in registering had no significant effect on Pakpak Bharat district's regional tax income, the MSME taxpayer's compliance in re-depositing tax returns had no significant effect on Pakpak Bharat district's regional tax revenue, The compliance of MSME taxpayers in calculating and payment of tax owed does not have a significant effect on regional tax revenues in Pakpak Bharat district, Compliance of MSME taxpayers in paying arrears has a significant effect on regional tax revenues of Pakpak Bharat district, Compliance of MSME taxpayers in registering, Compliance of MSME taxpayers in re-depositing tax returns, Compliance of MSME taxpayers in calculating and paying taxes owed, and Compliance of MSME taxpayers in paying arrears simultaneously has a significant effect on regional tax revenues in Pakpak Bharat district.